2017
DOI: 10.1002/bio.3282
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of AlN: Eu2+ green phosphors by a simple direct nitridation method

Abstract: Eu-doped aluminum nitride phosphors were successfully prepared using simple direct nitridation of a metallic aluminum and Eu O powder mixture in flowing ammonia. AlN formed at reaction temperatures >900°C, and Eu transformed into the secondary oxide phase EuAl O in the nitridation condition. Phase pure AlN was obtained by post-heat treatment of the nitridated product at 1600°C for 3 h in a nitrogen atmosphere, with an Eu doping concentration < 0.5%. The phosphors exhibited broad green emission centered at 521 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…00‐26‐1125) was detected. The Eu 3+ in the starting material Eu 2 O 3 could be reduced to Eu 2+ in the nitridation process, due to the reductive atmosphere of ammonia . Furthermore calcination led to the formation of EuAl 12 O 19 by reaction of alumina and EuO, that was the reason why alumina phase was absent in postcalcinated product.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…00‐26‐1125) was detected. The Eu 3+ in the starting material Eu 2 O 3 could be reduced to Eu 2+ in the nitridation process, due to the reductive atmosphere of ammonia . Furthermore calcination led to the formation of EuAl 12 O 19 by reaction of alumina and EuO, that was the reason why alumina phase was absent in postcalcinated product.…”
Section: Resultsmentioning
confidence: 99%
“…Direct nitridation of metallic aluminum in N 2 and/or NH 3 gas is a commercial route to prepare AlN powders, which shows advantage of simplicity, low‐cost, and nontoxicity . Compared with the CRN method, direct nitridation eliminates the problem of carbon residue.…”
Section: Introductionmentioning
confidence: 99%
“…There have been experimental efforts to understand the luminescent properties of AlN‐based phosphors . It was demonstrated that Eu, Si co‐doped AlN phosphor shows a strong blue luminescence by UV or electron excitation .…”
Section: Introductionmentioning
confidence: 99%